2020
DOI: 10.3389/fphar.2020.594474
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Use and the Risk of Major Adverse Cardiovascular Events in Patients Without Known Cardiovascular Disease: A Retrospective Cohort Study

Abstract: Aims: Conflicting data exist on whether an association exists between antidepressants and the risk of major adverse cardiovascular events (MACEs) in patients with depression. This may be due to the use of various study designs and residual or unmeasured confounding. We aimed to assess the association between antidepressant use and the risk of MACEs while considering various covariates, including severity of depression and the cardiovascular disease (CVD) risk score.Methods: Patients newly diagnosed with depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 34 publications
0
19
2
3
Order By: Relevance
“…For example, our findings differ from an observational study conducted in patients with newly diagnosed depression which compared the risk of MACE between TCAs versus non‐users of antidepressants 7 . That study found the use of TCAs to be associated with a modestly increased risk of MACE (HR: 1.20 [95% CI: 1.03, 1.40]) 7 . Likewise, in another study of adults with obesity and depression, compared to non‐use of antidepressants, use of TCAs (HR: 1.26 [95% CI: 1.01, 1.58]) was associated with increased risk of cardiovascular events 8 .…”
Section: Discussioncontrasting
confidence: 99%
“…For example, our findings differ from an observational study conducted in patients with newly diagnosed depression which compared the risk of MACE between TCAs versus non‐users of antidepressants 7 . That study found the use of TCAs to be associated with a modestly increased risk of MACE (HR: 1.20 [95% CI: 1.03, 1.40]) 7 . Likewise, in another study of adults with obesity and depression, compared to non‐use of antidepressants, use of TCAs (HR: 1.26 [95% CI: 1.01, 1.58]) was associated with increased risk of cardiovascular events 8 .…”
Section: Discussioncontrasting
confidence: 99%
“…Sex and age were assessed at index date. Arterial hypertension, dyslipidemia, chronic obstructive pulmonary disease (COPD) or asthma, diabetes, depression [ 20 , 21 ], and neoplasia were identified as comorbidities of interest at index date and within the previous year (see Table S1 for identification criteria).…”
Section: Methodsmentioning
confidence: 99%
“…Por el contrario, los antidepresivos tricíclicos (ADTs) se han relacionado con un efecto arritmogénico en pacientes con EAC o arritmias ventriculares, y también, se han asociado con aumento de los ECVs adversos mayores en pacientes con ECVA conocida de base, 7 incluso con dosis diarias definidas como bajas (dosis de amitriptilina menores a 37,5 mg/día, por ejemplo) y en aquellos sin ECVA. 8 Este efecto se puede explicar por la disminución de la variabilidad de la frecuencia cardiaca y prolongación del QT, que favorece la aparición de arritmias cardiacas (bloqueo de los canales iónicos de Na + , Ca 2+ , K + ). Estudios han demostrado que el uso de ADTs se hace en promedio por más de 365 días, y los ECVs adversos mayores aparecen a los 410 días en promedio.…”
Section: Métodosunclassified
“…Estudios han demostrado que el uso de ADTs se hace en promedio por más de 365 días, y los ECVs adversos mayores aparecen a los 410 días en promedio. 8 Un estudio de cohortes 7 evidenció que, en pacientes depresivos con EAC, el uso de ADTs, ISRSs, y antidepresivos atípicos (con excepción de los inhibidores de la recaptación de serotonina-norepinefrina), comparados con placebo, se asociaron con más ECVs adversos mayores. Llama la atención entonces como los ISRSs, siendo los más prescritos y de primera línea en ECV, no están exentos de desenlaces cardiovasculares, aunque se requiere mayor evidencia al respecto.…”
Section: Métodosunclassified
See 1 more Smart Citation